Upaya Penanggulangan Oleh Masyarakat dalam Membantu Pencegahan Tindak Pidana Pencurian Kelapa Sawit di Desa Markanding - Mhd Badri; Sumaidi Sumaidi; Reza Iswanto (Wajah Hukum, 2022)
The crime of palm oil theft now often occurs, especially in Markanding Village, so that efforts are needed to overcome it from the local community so that the crime of palm oil theft does not continue to increase. Therefore, the type of research in this study is empirical juridical which is carried out directly in the field with the research specification being descriptive with the data sources being research and literature. Therefore, the research approach is a conceptual approach in which data collection techniques using interviews and data analysis are carried out qualitatively. Thus, the results of the study, namely the prevention efforts by the community in helping to prevent the crime of palm oil theft in the Markanding Village are to provide appeals and advice to the perpetrators so as not to repeat the crime of palm oil theft and the people of Markanding Village also remind the security guards at the coconut harvesting place. to be more vigilant because there has been a criminal act of palm oil theft at the collection point of oil palm harvests and the obstacles in carrying out countermeasures by the community in helping to prevent the crime of palm oil theft in Markanding Village are the lack of legal awareness of the perpetrators themselves so that the perpetrators are still committed a crime of palm oil theft, the people of Markanding village still do not want to report and become witnesses related to the criminal act of palm oil theft.